Pharmaceutical Care in Saudi Hospitals: An Analytical Assessment of Its Impact on Patient Safety and Treatment Outcomes - Tumaihi, Hasan Yahya Buhi; Aldaoud, Waleed Abdullah; Asiri, Abdulrhman Ahmad Hassan; Alzahrani, Faisal Ahmad Mohammed; Alharbi, Sultan Jaza; Hammad, Mohammed Ali bin; Alghamdi, Mohammed Khalaf Mohammed; Enazi, Abdulrahman Gobile Al; Alharbi, Majed Farhan; Alshammari, Mohammed Awad; et al. (Journal of Posthumanism, 2024)
This analytical assessment examines the impact of pharmaceutical care on patient safety and treatment outcomes in Saudi hospitals, where the practice is still evolving and not uniformly specified in regulations. Hospitals form an ideal platform for implementing pharmaceutical care because of their patient caseloads, the complexity of medication use, and the need for interprofessional collaboration. Consequently, the impacts of pharmaceutical care on patient safety and treatment outcomes within Saudi hospitals are revisited. The assessment indicates that improved patient safety is coupled with reduced adverse outcomes for patients with chronic conditions, while the optimization of treatment regimens leads to a decrease in economic burden. Care models based on medication therapy management, clinical pharmacy, and team collaboration are outlined, as is the role of data analytics and human factors in enhancing safety. Further examination of effective practices in care delivery reveals a growing impetus to broaden services from primarily community settings into hospital-based practice. Gaps and challenges include workforce capacity, retention, policy enforcement, and cultural barriers Pharmaceutical Care in Saudi Hospitals: An Analytical Assessment of Its Impact on Patient Safety and Treatment Outcomes.